Analis Kemampuan Menulis Teks Eksposisi Siswa Kelas V SD - Nurrahma Zulita; Chandra Chandra; Inggria Kharisma (Pusat Riset dan Inovasi Nasional, 2025)
This study aims to describe the ability to write exposition texts for 5th grade elementary school students, before and after the implementation of the Think-Pair-Share strategy. This study uses a descriptive qualitative approach. The subjects of the study were 7 5th grade students of SD Negeri which totaled 7 students. Data is collected through observation of the learning process and analysis of students' writing. The results showed that before the implementation of the Think-Pair-Share strategy, most students had the ability to write exposition texts in adequate categories. After the implementation of the Think-Pair-Share strategy, there was an increase in students' ability to write exposition texts, with most students in the good category. This study concludes that the Think-Pair-Share strategy can make a positive contribution in improving the ability to write exposition texts for grade 5 elementary school students